Concordance between TP53 alterations in blood and tissue: impact of time interval, biopsy site, cancer type and circulating tumor DNA burden. Issue 6 (7th April 2020) - Bieg‐Bourne, Cheyennedra C.; Okamura, Ryosuke; Kurzrock, Razelle
Abstract : We examined the impact of spatial, temporal, histologic, and quantitative factors on concordance between TP53 alterations in tissue DNA vs in circulating tumor DNA (ctDNA). Four hundred and thirty‐three patients underwent next‐generation sequencing (NGS) in which both tissue and blood samples were evaluated. TP53 was detected in 258 of 433 patients (59.6%); 215 had tissue TP53 alterations (49.7%); 159, ctDNA (36.7%); and 116, both tissue and ctDNA (27.8%). Overall concordance rate between ctDNA and tissue biopsies for TP53 alterations was 67.2%; positive concordance was 45.0%. Overall concordance for TP53 did not vary among patients with ≤ 2 months vs > 6 months between test samples; however, positive concordance trended higher when time intervals between test samples were shorter, suggesting that the lack of difference in overall concordance may be due to the large number of negative/negative tests. There was a trend toward higher overall concordance based on biopsy site (metastatic vs primary) ( P  = 0.07) and significantly higher positive concordance if the tissue biopsy site was a metastatic lesion ( P  = 0.03). Positive concordance significantly decreased in noncolorectal cancer patients vs colorectal cancer patients ( P  = 0.02). Finally, higher %ctDNA was associated with higher concordance rates between blood and tissue ( P  < 0.001). Taken together, these data indicate that both blood and tissue DNA sequencing are necessary to evaluate the full scope of TP53 alterations, and that concordance rates may be related to multiple factors including, but not limited to, amount of ctDNA, histologic context, and site of tissue biopsy. Abstract : This study presents evidence that the evaluation of the full spectrum of TP53 alterations in patients with diverse malignancies requires sequencing of both blood‐derived circulating tumor DNA and tissue DNA. Multiple factors can influence positive concordance rates between the tests, including site of tissue biopsy, %ctDNA, time between tissue biopsy and blood sample, and histologic context.